Several Remarks on Contemporary Ukrainian Lyrical Poetry under Fire Attacks - Ковалів, Юрій (International Studies. Interdisciplinary Political and Cultural Journal, 2024)
In the paper, the author, referring to the real situation in the contemporary poetry during the new round of the Russian-Ukrainian war refutes the famous Cicero’s saying “Inter arma, silent Musae” (En. “When arms speak, Muses are silent”). After February 24th, a powerful rise of the mobile genre happened due to the emergence of the psychotype of the passionary, who, nourished by historical and ethnomental memory, motivates historically-justified resistance to the Moscow aggressor, defending his home, family, land, and human and national dignity. He became the main lyrical hero of the contemporary Ukrainian poetry, among the authors of which there are many soldiers of the Armed Forces of Ukrainian, Territorial Defence troops, hospitallers, volunteers, as well as exiles and eyewitnesses of the national verge of life and death due to heroic actions and suffering. The primary importance is given to the resistive energy of the Word, which can be journalistically appealing and formulaically rhetorical. However, it is deeper and more important when it focuses on understanding the specific features of military reality, personally experienced by each author, which often acquire convincing generalisations, philosophical meditations, which in poetic form comprehend the passionate ontology of the inalienable Ukrainian people with the intention to eliminate the destructive forces of Moscow. The author states that it does not matter which verse forms are chosen – faceted quatrains or flexible verlibriums. In the paper, the author has highlighted the panorama of the contemporary Ukrainian poetry, analysing its specific genre and style features, clarifying the creative potential of the poetic word in the harsh circumstances of the war, a new thoroughly filled page of Ukrainian literature. The poetry in Ukraine in the situation of the Russian-Ukrainian war, refuting Cicero’s aphorism, acquired a new paradigm of senses and expectations. Immersed in the objective specifics of everyday life at the front, suffering, trials on the border of life and death, it testified to a new psychotype of the lyrical hero, analogous to his real prototype, who, defending his home, his family, his land, and human and national dignity, is motivated to resist the Moscow aggressor. The panorama of contemporary Ukrainian lyrics in its genre and stylistic diversity highlighted in the article gives reason to assert not only the inexhaustible creative potential of the most mobile genre-genre variety, but also a thoroughly filling new page of Ukrainian literature. The lyrical poetry on war discussed in this article is a part of the new cultural narrative of Ukraine that is oriented to re-think and reinforce the concepts of war and connected with this concept notions, e.g. pain, human catastrophe, human powers, dignity, human values, democracy, etc. The new narrative models and stylistic peculiarities of the contemporary Ukrainian lyrical texts have been analysed and systematised in this paper.